(untitled) (Comparative & International Education Series, 2022)
The COVID-19 pandemic brought a colossal challenge around the world, affecting all sectors of human affairs, including higher education. Due to a prolonged health crisis, colleges and universities in Nepal adopted online/remote teaching as an emergency response mechanism. Against this backdrop, this study examines remote teaching and learning practice and its efficacy and impacts on disadvantaged students in Nepal. Adopting semi-structured phone/online interviews with university students, we highlight the challenges of disadvantaged students’ unequal participation in higher education. It is argued that disadvantaged students in Nepali higher education have been profoundly impacted by the lack of digital preparedness and the dearth of proper student support and motivation mechanisms. If unprepared for effective responses, this can adversely affect students’ participation in higher education, engagement in learning, and completion of the university course cycle. Implications of the research findings are discussed concerning higher education systems’ justice and democratic values. How to cite in APA: Ghimire, S. N., Bhattarai, U., & Rajbhandari, J. (2022). Digital disconnect: An analysis of equity and social justice in Nepal’s higher education. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 69-84). STAR Scholars.